Mitigating the Impact of COVID-19 and Strengthening Health Systems in the Middle East and North Africa - Duran, Denizhan (World Bank, Washington, DC, 2020)
Almost every country in the Middle East and North Africa (MNA) region is faced with the increasing significant burden imposed by Coronavirus 2019 (COVID-19) on their health systems. The focus thus far has been on executing emergency interventions to prevent, detect, and respond to the COVID-19 epidemic. COVID-19 models for MNA countries indicate that the epidemic is far from its peak, indicating the emergency will remain for the foreseeable future and result in a reduction in demand for essential non-COVID-19 health services. MNA countries have a wide range of at-risk populations, which necessitate a longer-term, health system-wide approach to managing the COVID-19 pandemic in addition to the emergency projects prepared. This note describes the impact of COVID-19 on the health systems of countries in the MNA region as well as ways to mitigate this impact. It presents options to mitigate this impact, across relief, response, and recovery phases. This note presents a starting point for discussions across the region for priority health system strengthening areas.